Is the Elasticity of Taxable Income Mostly an Income Effect? - Xavier Dufour; Pierre-Carl Michaud; Michael Smart (CESifo GmbH, 2025)
We use variation in marginal tax rates and in tax bracket thresholds at which they apply in order to identify the substitution and income effects of tax reforms. We use a triple-difference estimator that exploits variation from subnational tax reforms, for which behavioral responses to taxes are identified even in the presence of unobservable shocks to the income distribution. While high-income taxpayers respond more to tax changes, our results suggest this reflects much more the income or salience effects of tax reforms, rather than inherent heterogeneity in substitution effects. We discuss the implications for optimal redistributive tax policies.
Keywords: D31; H21; H24; 330; income and substitution effects; tax salience; optimal progressivity